2007
DOI: 10.3727/000000007783464885
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell-Based Cell Therapy for Spinal Cord Injury

Abstract: Traumatic injuries to the spinal cord lead to severe and permanent neurological deficits. Although no effective therapeutic option is currently available, recent animal studies have shown that cellular transplantation strategies hold promise to enhance functional recovery after spinal cord injury (SCI). This review is to analyze the experiments where transplantation of stem/progenitor cells produced successful functional outcome in animal models of SCI. There is no consensus yet on what kind of stem/progenitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 89 publications
0
74
0
2
Order By: Relevance
“…45 F3.VEGF cells were derived from F3 human NSC line and known to give rise to both neurons and glial cells. 28,46 F3 human NSC line has been shown to improve clinical outcome following brain transplantation in animal models of stroke, 45,46 spinal cord injury, 47 Parkinson disease, 48 Huntington disease 49 and lysosomal storage disease. 50 We identified that 12% of intrathecally introduced F3.VEGF cells migrated into the spinal cord and 52% cells were found along the meninges of the lumbar spinal cord 4 weeks after the injection.…”
Section: Discussionmentioning
confidence: 99%
“…45 F3.VEGF cells were derived from F3 human NSC line and known to give rise to both neurons and glial cells. 28,46 F3 human NSC line has been shown to improve clinical outcome following brain transplantation in animal models of stroke, 45,46 spinal cord injury, 47 Parkinson disease, 48 Huntington disease 49 and lysosomal storage disease. 50 We identified that 12% of intrathecally introduced F3.VEGF cells migrated into the spinal cord and 52% cells were found along the meninges of the lumbar spinal cord 4 weeks after the injection.…”
Section: Discussionmentioning
confidence: 99%
“…Technically, these discrepancies may be caused in part by the use of peutic implantation of mesenchymal stem cells (MSCs), in particular, has been attempted in several clinical trials different cell labeling/tracking methods, cell administration protocols, timing of cell transplantation after tissue for hematological disorders, cardiovascular diseases, osteogenesis imperfecta, neurological pathologies, and even injury, and possibly misinterpretation of microscopy results (4). cancer therapy (9, 14,23). The ease of isolation, capacity for large-scale expansion, and alleged immunoprivileged Many cell labeling techniques have been used for tracking implanted stem cells in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The MFIs for CD90 cells were 9 552, 9 356 and 9 250; for nestin 3 620, son's and Alzheimer's disease, and amyothrophic lateral sclerosis), muscular dystrophy, myocardiopathies, and myocardial infarctions, belong to serious pathological conditions connected with high morbidity and mortality [6,10,13,21,22]. The treatment modalities of these diseases [3].…”
Section: Resultsmentioning
confidence: 99%
“…and with positive results, tested a modified method of harvesting and expansion of adult rat bone marrow MSCs enabling an easy autotransplantation to donors, thus avoiding possible adverse immune reaction [2,3,4,10,19,20].…”
Section: Introductionmentioning
confidence: 99%